Polyclinidae (Ascidiacea: Aplousobranchia) from the Gulf of Mexico, collected during the “Hourglass” cruises (1965–1967) - Fortaleza, M. T. V.; Lotufo, T. M. D. C. (Zootaxa, 2018)
This paper presents the ascidians from the Family Polyclinidae collected in the Gulf of Mexico during the Hourglass Cruises between August 1965 and November 1967. The analysis of the collected material revealed the presence of eight polyclinid ascidians from three different genera, with two new species and two new records for the Gulf of Mexico